Does COVID-19 affect small and medium enterprises' capital structure in vietnam? - Quoc Trung Nguyen Kim (Cogent Economics & Finance, 2023)
This study estimates the effect of COVID-19 on listed small and medium enterprises' capital structures in Vietnam from 2010 to 2020 by a dynamic panel model with 825 observations. Conducting the generalized method of moments, the findings show that COVID-19 is a significant factor affecting small and medium enterprises' capital structures. The current results are explained based on the signalling theory. Although the findings are consistent with the previous empirical studies indicating the capital structure and exploring its determinants in diverse ways, these studies are interpreted based on agency theory, pecking of order, trade-off theory. Furthermore, our results are robust to a series of endogeneity checks using an alternative method of regression.
Keywords: D24; J11; L21; 330; capital structure; COVID-19; signalling theory; Vietnam